Aggregation, segregation, and dispersal of homotypic germ plasm RNPs in the early zebrafish embryo. Issue 4 (4th March 2019) - Eno, Celeste; Hansen, Christina L.; Pelegri, Francisco
Abstract : Background: In zebrafish and many other organisms, specification of primordial germ cells (PGCs) requires the transmission of maternally‐derived germ plasm. Zebrafish germ plasm ribonucleoparticles (RNPs) aggregate along the cleavage furrows during the first several cell cycles, segregate asymmetrically during the cleavage stages, and undergo cytoplasmic dispersal in the late blastula. Results: For all tested germ plasm RNAs [ carbonic anhydrase 15b ( ca15b ), deleted in azoospermia‐like ( dazl ), dead end ( dnd ), nanos 3 ( nos3 ), regulator of G‐protein signaling14a ( rgs14a), and vasa/DEAD box polypeptide 4 (vasa/ddx4)], RNPs are homotypic (containing a single RNA type), with RNPs packing tightly yet remaining distinct within germ plasm aggregates. Homotypic clustering of RNAs within RNPs is observed before aggregation in the cortex and is maintained through germ plasm recruitment, asymmetric segregation and RNP dispersal. We also identify a step of germ plasm fragmentation during the cleavage stages that precedes RNP dispersal. Conclusions: Our findings suggest that germ plasm aggregates act as subcellular compartments that temporarily collect and carry single RNA‐type RNPs from fertilization until their cytoplasmic dispersal in PGCs at the end of the blastula period, and describe a previously unknown fragmentation step that allows for an increase in the pool of germ plasm‐carrying cells, presumably PGCs. Developmental Dynamics 248:306–318, 2019. © 2019 Wiley Periodicals, Inc. Key Findings: Zebrafish germ plasm RNPs are largely homotypic. Fragmentation of RNP aggregates increases the pool of germ plasm‐carrying cells. RNPs appears to remain intact through aggregate recruitment, segregation and cytoplasmic dispersal.